2014
DOI: 10.1590/1414-431x20133353
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human cytomegalovirus DNA in various blood components after liver transplantation

Abstract: The quantification of human cytomegalovirus (HCMV DNA) by real-time PCR is currently a primary option for laboratory diagnosis of HCMV infection. However, the optimal sample material remains controversial due to the use of different PCR assays. To explore the best blood component for HCMV DNA surveillance after liver transplantation, whole blood (WB), serum (SE), and plasma (PL) specimens were collected simultaneously from targeted patients and examined for HCMV DNA using one commercially available assay. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…HCMV viremia is mostly cell associated [ 3 ]. HCMV DNA has been found in serum and plasma of infected transplant recipients, but these are highly fragmented genomes implying that they are not infectious virions [ 55 , 56 ]. In support of cell-associated viremia, depletion of leukocytes from blood products derived from seropositive donors prior to blood transfusion prevents HCMV transfer [ 57 , 58 ].…”
Section: Cell-mediated Disseminationmentioning
confidence: 99%
“…HCMV viremia is mostly cell associated [ 3 ]. HCMV DNA has been found in serum and plasma of infected transplant recipients, but these are highly fragmented genomes implying that they are not infectious virions [ 55 , 56 ]. In support of cell-associated viremia, depletion of leukocytes from blood products derived from seropositive donors prior to blood transfusion prevents HCMV transfer [ 57 , 58 ].…”
Section: Cell-mediated Disseminationmentioning
confidence: 99%
“…PCR testing on the 28 samples from patients in whom two or more reads of CMV were detected by rWGS was done on DNA extracted from whole blood samples rather than on plasma as is traditionally done when CMV viremia is suspected. However, the common practice of obtaining plasma CMV PCR in the clinical setting is not necessarily due to a limitation in detection of CMV from whole blood 24,25 . Additionally, given the negative qPCR results for the majority of patients with only 2 reads of CMV and the positive correlation between read count and higher Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that DNA extracted from whole blood was more representative of Epstein-Barr virus burden in human circulation than was DNA extracted from serum or plasma (Stevens et al 2001). In humans, DNA extracted from leukocytes provided a larger number of PCR-positive results than that extracted from plasma for the detection of EpsteinBarr virus (Ito et al 2016) and cytomegalovirus (Deback et al 2007;Chen et al 2014). In 2 groups of humans, a larger number of samples tested positive for herpes virus-6 DNA by PCR using DNA extracted from blood mononuclear cells (66.7% and 41.46%) compared with DNA from serum (60.3% and 14.6%), but the amounts of DNA (copies/mL) were lower in blood cells (165 and 157) than in plasma (264 and 192) (Ramroodi et al 2013).…”
Section: Discussionmentioning
confidence: 99%